Implementation of the E-Ktp Service Pick-Up Program for the Disabled and Elderly in Bangkalan Regency - Muhammad Aryya Maulana; Muhammad Agus Muljanto (Pengurus Pusat Perkumpulan Ilmuwan Administrasi Negara Indonesia (PIANI), 2026)
Population administration services are a basic human right that must be fulfilled fairly and inclusively by the state. However, the elderly and people with disabilities often face barriers in obtaining e-KTP services due to limited mobility and geographic distance. This study aims to analyze the implementation of the Jemput Bola Program e-KTP services as an effort to improve population administration services for the elderly and people with disabilities in Bangkalan Regency. This program provides direct services to the homes of the elderly and people with disabilities without having to come to the Dispendukcapil office or sub-district office. This study uses a qualitative method with a descriptive approach. Data collection techniques were carried out through interviews, observation, and documentation, and their validity was tested through data triangulation. The research analysis uses George C. Edwards III's policy implementation theory which includes four main dimensions, namely communication, resources, disposition, and bureaucratic structure. The results of the study show that of the four dimensions, some of them have not been implemented optimally, such as the dimensions of communication, resources, and bureaucratic structure. The researcher's recommendations for this program include increasing the socialization of the Jemput Bola program more evenly and inclusively, increasing the number of implementing officers, and implementing the results of the monthly evaluation in a concrete and sustainable manner.